2018
DOI: 10.1128/aac.02323-17
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pharmacokinetic/Pharmacodynamic Relationship of Relebactam (MK-7655) in Combination with Imipenem in a Hollow-Fiber Infection Model

Abstract: Resistance to antibiotics among bacterial pathogens is rapidly spreading, and therapeutic options against multidrug-resistant bacteria are limited. There is an urgent need for new drugs, especially those that can circumvent the broad array of resistance pathways that bacteria have evolved. In this study, we assessed the pharmacokinetic/pharmacodynamic relationship of the novel β-lactamase inhibitor relebactam (REL; MK-7655) in a hollow-fiber infection model. REL is intended for use with the carbapenem β-lactam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…For selected dosing regimens ( Table ), joint PTA was assessed based on the established imipenem efficacy target criteria of 6.5% f T > MIC and the relebactam efficacy target criteria of f AUC 0–24 hours /MIC ≥ 5.2 . Imipenem and relebactam free fractions in human plasma (0.80 and 0.78, respectively) were used to simulate unbound concentrations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For selected dosing regimens ( Table ), joint PTA was assessed based on the established imipenem efficacy target criteria of 6.5% f T > MIC and the relebactam efficacy target criteria of f AUC 0–24 hours /MIC ≥ 5.2 . Imipenem and relebactam free fractions in human plasma (0.80 and 0.78, respectively) were used to simulate unbound concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro susceptibility and hollow fiber (HF) time‐kill studies found that relebactam restored the activity of subinhibitory concentrations of imipenem against imipenem‐resistant isolates . Animal studies further confirmed the activity of relebactam, and integrated translational pharmacokinetic/pharmacodynamic (PK/PD) modeling suggested that the combination of imipenem/relebactam would be efficacious against the majority of imipenem‐resistant strains at clinically achievable doses and concentrations .…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…78,79 Researchers studied the pharmacokinetics and pharmacodynamics of IMI-REL against K. pneumoniae, E. coli, S. marcescens, and P. aeruginosa in an in vitro hollow-fiber model. 79 In their model, they determined that the best marker of IMI-REL efficacy was imipenem time above dynamic imipenem MIC. Dynamic MIC values for imipenem were calculated by determining imipenem MIC values in the presence of varying levels of relebactam based on their simulated dosing regimens.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…As our understanding of the mechanism of action and PD parameters that govern BLI continues to improve, it is crucial that each newly developed BLI undergo a thorough PK/PD evaluation in combination with several potential BL agents of interest in order to establish the PK/PD driver of efficacy and determine thresholds for bactericidality and suppression of resistance for that specific BL-BLI combination. This is highlighted by the discordance in PK/PD drivers observed for avibactam compared to vaborbactam and relebactam [32] despite their similar spectrums of activity and may contribute, in part, to the emergence of resistance observed, albeit infrequently, during clinical use of ceftazidime-avibactam [33]. As use of meropenem-vaborbactam increases, future real-world clinical outcomes data will help determine if these PK/PD advantages translate into improved outcomes for these difficult-to-treat infections.…”
Section: Pharmacodynamicsmentioning
confidence: 99%